1997
DOI: 10.1046/j.1365-3148.1997.d01-31.x
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of Del (D‐elute) using polymerase chain reaction (PCR) with RHD gene‐specific primers

Abstract: Del (D-elute) in the Rh blood group system is a variant with very weak D antigen and no agglutination is found by the indirect antiglobulin test. This variant is characterized by the presence of anti-D eluate obtained after an adsorption-elution test using anti-D antibodies. We studied here the molecular genetic status of Del by using polymerase chain reaction with sequence-specific primers (PCR-SSP). We screened 306 serologically apparent D-negative Japanese donors comprising 102 Del types for exons 7, 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 9 publications
0
28
0
2
Order By: Relevance
“…Most DEL donors are typed as RhD-negative because the routine serological typing does not distinguish RhD-negative from the DEL phenotype. Previous reports have indicated that the presence of the RHD gene in DEL samples seems to relate strictly to the RhC phenotype with high incidence of RhC(+) in the apparent RhD-negative persons [12, 16, 17]. All DEL persons with intact RHD gene showed the CC or Cc phenotype but not the cc phenotype.…”
Section: Introductionmentioning
confidence: 90%
“…Most DEL donors are typed as RhD-negative because the routine serological typing does not distinguish RhD-negative from the DEL phenotype. Previous reports have indicated that the presence of the RHD gene in DEL samples seems to relate strictly to the RhC phenotype with high incidence of RhC(+) in the apparent RhD-negative persons [12, 16, 17]. All DEL persons with intact RHD gene showed the CC or Cc phenotype but not the cc phenotype.…”
Section: Introductionmentioning
confidence: 90%
“…Less than 1% of Chinese Han are RhD-negative (Gu et al , 2014; Yang et al , 2007) and of these, as many as 30% express the DEL phenotype (Shao et al , 2002, Wagner et al , 2005). In Japanese, 0.5% are RhD-negative (Okubo et al , 1991) and 28% of these express a DEL phenotype (Fukumori et al , 1997). In Koreans, 0.15% are RhD-negative and of these, 17% express a DEL phenotype (Kim et al , 2005, Lüttringhaus et al , 2006).…”
Section: A Serological Weak D Phenotype Is the Expression Of An Aminomentioning
confidence: 99%
“…Вариантом антигена D, не распознаваемым моно-клональными анти-D-реактивами, но идентифициру-емым методами адсорбции-элюции [37], является фенотип DEL (D el ), часто встречающийся у предста-вителей монголоидной расы [38][39][40]. Молекулярная основа данного варианта гена RHD -делеция 1013 пар оснований между интронами 8 и 9, выпадение почти всего экзона 9 и присутствие аллеля 1227А [41,42].…”
Section: O N C O G E M a T O L O G Y 3 ' 2 0 1 5 V O L 10unclassified